Fast transient boundary control and steady-state operation of the dual active bridge converter using the natural switching surface - Oggier, German Gustavo (2014)
This paper presents a boundary control scheme for Dual Active Bridge (DAB) converters using the Natural Switching Surface (NSS). The implementation of a curved switching surface for DAB converters is a new area of research undertaken in this work. The proposed technique brings the benefit of unprecedented dynamic performance, already developed for non-isolated topologies (e.g., buck and boost), to this more complex isolated topology. The analysis provides insight into the natural trajectories of the DAB converters and creates an accurate framework in the normalized geometrical domain. As a result, the physical limits of the converter under study become evident. Those physical limits are exploited by employing the NSS to obtain fast transient response under start-up, sudden load transients, and reference change. In addition, fixed-frequency operation is one of the key features of the proposed control scheme which allows optimizing the design of the high-frequency transformer. Experimental results are presented to validate the NSS for DAB converters and illustrate the benefits of the normalization technique.